2011
DOI: 10.1097/mbc.0b013e328349f1d6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of an international sensitivity index of thromboplastin reagents using a WHO thromboplastin as calibrator for plasma spiked with rivaroxaban

Abstract: Rivaroxaban and other direct factor Xa inhibitors are used at fixed doses without drug monitoring and dose adjustment. Patients may require determination of the anticoagulant effect during treatment. The aim of this study was to develop a method to reduce the differences between thromboplastin reagents and coagulation analysers for determination of the anticoagulant effect of rivaroxaban in human plasma. Purity of rivaroxaban extracted from commercially available drug was confirmed by mass spectrometry, elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…Moreover, standardization as assessed in a collaborative survey is poor: the average interlaboratory variation of results obtained while measuring the same rivaroxaban-spiked plasmas by means of local methods was high (ie, 25%). 18 Conversely, the PT is readily available even in an emergency and its standardization could be obtained as described 19,20 by expressing results as PT ratio (patientto-normal) corrected by means of a sensitivity index. Such an index can be determined for working thromboplastins relative to an international standard.…”
Section: Potentially Useful Othersmentioning
confidence: 99%
“…Moreover, standardization as assessed in a collaborative survey is poor: the average interlaboratory variation of results obtained while measuring the same rivaroxaban-spiked plasmas by means of local methods was high (ie, 25%). 18 Conversely, the PT is readily available even in an emergency and its standardization could be obtained as described 19,20 by expressing results as PT ratio (patientto-normal) corrected by means of a sensitivity index. Such an index can be determined for working thromboplastins relative to an international standard.…”
Section: Potentially Useful Othersmentioning
confidence: 99%
“…In contrast to dabigatran, the PT is more generally sensitive to rivaroxaban than the aPTT, although differential reagent sensitivity is observed. 4,19,24,25,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] All TT and ecarin-based assays (i.e., standard TT, dTT, HTI, ECT, and ECA) are insensitive to rivaroxaban. 24,35,55,61,63 The PICT assay was also reported as sensitive, although this assay may require some major degree of optimization.…”
Section: Rivaroxabanmentioning
confidence: 99%
“…As the PT assay is sensitive to the prothrombinase complex, the PT is influenced by rivaroxaban in a concentration-dependent manner with an increase in seconds [4][5][6]. Because the PT assay is widely available in routine clinical laboratories and known as monitoring system for vitamin K antagonists, there have been attempts to use this test method to monitor rivaroxaban and even to adapt the INR system for this new oral factor Xa inhibitor [7]. However, it has been shown that the classical INR fails to correct the thromboplastin variability in response to rivaroxaban.…”
Section: Interference Of Anticoagulants On Coagu Lation Assays and Mementioning
confidence: 99%